2021
DOI: 10.1038/s41598-021-98582-9
|View full text |Cite
|
Sign up to set email alerts
|

Mitigating multiple stresses in Pangasianodon hypophthalmus with a novel dietary mixture of selenium nanoparticles and Omega-3-fatty acid

Abstract: Effects of a novel dietary mixture of selenium nanoparticles (Se-NPs) and omega-3-fatty acids i.e., Eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) on mitigating arsenic pollution, high-temperature stress and bacterial infection were investigated in Pangasianodon hypophthalmus. To aim this, four isocaloric and iso-nitrogenous diets were prepared: control feed (no supplementation), Se-NPs at 0.2 mg kg−1 diet with EPA + DHA at 0.2, 0.4 and 0.6% as supplemented diets. Fish were reared under normal cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 113 publications
(128 reference statements)
0
10
0
Order By: Relevance
“…Recently, intelligent approaches have been widely utilized for modeling thermal and hydrodynamic characterizations of various systems 53 , 54 . The multilayer perceptron (MLP) is the most famous approach among several available neural networks, which has been broadly used for modeling complex systems 55 58 . Figure 1 shows the configuration of the present MLP network for modeling of two-phase FPD in coiled tubes.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, intelligent approaches have been widely utilized for modeling thermal and hydrodynamic characterizations of various systems 53 , 54 . The multilayer perceptron (MLP) is the most famous approach among several available neural networks, which has been broadly used for modeling complex systems 55 58 . Figure 1 shows the configuration of the present MLP network for modeling of two-phase FPD in coiled tubes.…”
Section: Methodsmentioning
confidence: 99%
“…To our best knowledge, in fish, Total protein, Albumin, and Globulin are known as important components of the innate immune system (Rao et al, 2006). Albumin is needed for the transportation of metal, hormones, vitamins, drugs, bilirubin, and fat metabolites and regulates the free available hormones and is mainly secreted from the liver in fish to fulfill the high energy demand during stress through protein synthesis (Abdel-Tawwab and Ahmad, 2009;Kumar et al, 2021). In the present investigation, the Albumin was less than Globulin, however rapid utilization of Albumin to meet the immediate energy demand could also increase its rate of synthesis in the liver.…”
Section: Discussionmentioning
confidence: 57%
“…However, in some cases, no significant differences were observed between Chlorella vulgaris dry powder treatments while in many immunity indices; the highest indices were observed in the fish fed with a diet containing the 5% Chlorella vulgaris dry powder level. The primary stress response is Cortisol which is elevated in fish exposed to poison and high temperature (Kumar et al, 2021). Imidacloprid can target several sites on a hypothalamuspituitary-internal axis which might be the reason for increased Cortisol secretion in this study.…”
Section: Discussionmentioning
confidence: 69%
“…Like in mammals, GCs are a major stress hormone in fish and are secreted by the hypothalamic–pituitary–inter-renal (HPI) axis, analogous to the HPA axis in mammals [ 237 , 238 ]. One study found that treatment of iridescent sharks ( Pangasianodon hypothalamus ) with selenium nanoparticles effectively protected against raised cortisol levels following arsenic and heat stress [ 239 ]. A contrasting result was found in gilthead seabream ( Sparusaurata ), where long-term supplementation with hydroxy-selenomethionine (OH-SeMet) resulted in elevated plasma cortisol levels following a crowding stress test [ 240 ].…”
Section: Signals From Brain To Bodymentioning
confidence: 99%